Genetic Variability, Diversity, Heterosis and Combining Ability in Sponge Gourd [Luffa cylindrica (Roem.) L.] - Kumar, J. Suresh; Pandit, M. K. (International Journal of Bio-resource and Stress Management, 2022)
This experiment was conducted at Mandouri farm, Horticultural Research Station, Bidhan Chandra Krishi Viswavidyala (BCKV), West Bengal, India during March, 2014 to July, 2018. The objectives of the research were to determine genetic variability, phenotypic performance and diversity for yield and 17 yield attributing traits of the 45 sponge gourd germplasm. To study the heterosis and combining ability of parental lines with half diallel analysis for earliness and yield contributing characters. PCV (phenotypic coefficient of variation) was higher than GCV (genotypic coefficient of variation) for all the traits studied. Higher PCV and GCV were recorded for traits namely number of primary branches plant-1, number of fruiting nodes on main stem, sex ratio (male/female), fruits plant-1 and fruit yield plant-1. Based on Mahalanobis’ D2 statistic, the genotypes of sponge gourd were grouped into 7 different clusters. Fruit yield plant-1, weight of fruit and number of fruiting nodes on main stem had maximum contribution towards genetic divergence. Among the parents, Patna Local, IC-336759 and IC-284795 showed high significant positive GCA effects as well as per se performance for yield and yield related attributes. Additive as well as non-additive gene action regulating the different traits. The traits under non additive gene action. The magnitude of standard heterosis was found in desirable direction for early and yield traits viz., days to first pistillate flower appearance in the cross IC284795×Patna Loca (-23.07%), for 50% flowering in the cross IC-284795×Patna Local (-18.89%), sex ratio in the cross IC-336759×Patna Local (-53.41%), for number of fruit vine-1 in the cross IC-284795×Patna Local (34.56%) and average fruit weight in the cross IC336759×Patna Local (110.09%). Promising germplasm Patna Local may be subjected for regional yield trail along with released variety with a view to develop new variety of sponge gourd. The superior hybrids can be exploited for hybridization programme.